Comparison of Human Immunodeficiency Virus Type 1 Tropism Profiles in Clinical Samples by the Trofile and MT-2 Assays - Coakley, Eoin; Reeves, Jacqueline D.; Huang, Wei; Mangas-Ruiz, Marga; Maurer, Irma; Harskamp, Agnes M.; Gupta, Soumi; Lie, Yolanda; Petropoulos, Christos J.; Schuitemaker, Hanneke; van 't Wout, Angélique B. (Antimicrobial Agents and Chemotherapy, 2009)
Classifications Services AAC Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue AAC About AAC Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy AAC RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0066-4804 Online ISSN: 1098-6596 Copyright © 2014 by the American Society for Microbiology. For an alternate route to AAC .asm.org, visit: AAC